Fiddling with fate - Kelly, Diane (Kelly, Diane. Southern homebrew mystery., 2023)
It's August in Chattanooga, Tennessee and moonshiner Hattie Hayes has collaborated with a nearby vineyard to serve her moonshine at a Wine and 'Shine event. Not only is this an opportunity for Hattie to gain more moonshine fans, but she's also excited to hear the Bootlegging Brothers, a popular bluegrass band. But not every attendee is looking for harmony. When one of the brothers disappears and is presumed dead, Hattie realizes her grace note gathering has suddenly turned more sour than her mash.